Peroxidase responses of two contrasting Medicago ciliaris populations to cold stress in aerial and root systems - Yahia N.; Bouira A.; Cheriet C.; Fyad-Lameche F.Z. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Effect of cold on antioxidant responses in aerial (shoots and leaves) and roots tissues of two contrasting accessions of Medicago ciliaris Krockers (Cil 126, tolerant and Cil 123, sensible) seedling were investigated. Ten-day-old grown seedlings were subjected at different periods of cold acclimation (4 °C) 2, 4, and 6 days. Peroxidase (EC 1.11.1.7) (POD) activities and isoenzymes expression of plantlets treated and control (23 °C) of the aerial (shoot + leaves) and root systems were carried. Global peroxidase activity under low temperature stress was higher in tolerant ecotype than sensible one. The same trend was also observed at expressed isoenzymes. On the other hand, whether in tolerant or sensitive, activity and isoenzymes peroxidase was more pronounced at the root than in aerial system.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)